Investigation of the role of Free DNA in the formation of Bacterial Biofilm - Sarker, Anusree; Mayesha, Iffat Islam (Brac University, 2023)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2022.